Development of a Rapid Method for Residence Time Distribution Measurement in Twin-Screw Wet Granulation Based on Image Processing with Lab Color Space - Jie Zhao; Geng Tian; Ying Tian; Haibin Qu (Pharmaceutics, 2025)
Background/Objectives: In the twin-screw wet granulation (TSWG) process, accurate measurement of residence time distribution (RTD) is critical, as it characterizes material transport kinetics and mixing behavior. It plays a critical role in evaluating the homogeneity and stability of the granulation process and optimizing process parameters. It is necessary to overcome the limitations arising from the complex and time-consuming procedures of conventional RTD determination methods. Methods: This study proposes a new RTD detection method based on image processing. It uses black dye as a tracer to obtain RTD curve data, and the effects of process parameters such as tracer dosage, screw speed, and feeding rate on the RTD were investigated. Results: The results show that the established method can accurately determine RTD and that the tracer dosage has no significant effect on the detection results. Further analysis revealed that the screw speed is negatively correlated with the mean residence time (MRT). As the speed increases, not only does the MRT shorten, but its distribution also decreases. Similarly, an increase in the feeding rate also leads to a decrease in the MRT and distribution, but it is worth noting that lower feeding rates are beneficial for achieving a state close to mixed flow, while excessively high feeding rates are not conducive to sufficient mixing of materials in the extruder. Conclusions: The RTD detection method provides a reliable parameter basis and theoretical guidance for the in-depth study of the TSWG process and the development of quality control strategies.